2014
DOI: 10.1166/jnn.2014.9989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ag Nanowire Addition Into Nanoparticle Paste on the Conductivity of Ag Patterns Printed by Gravure Offset Method

Abstract: This paper focuses on the effect of Ag nanowire addition into a commercial Ag nanopaste and the printability evaluation of the mixed paste by the gravure offset printing methodology. Ag nanowires were synthesized by a modified polyol method, and a small amount of them was added into a commercial metallic paste based on Ag nanoparticles of 50 nm in diameter. Two annealing temperatures were selected for comparison, and electrical conductivity was measured by four point probe method. As a result, the hybrid mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We found that the conductivity of the formed patterns relies on the concentration of AgNW. The resistance of the pure Ag pattern has a relatively high value because of electron scattering at the many contact points of the Ag granules, whereas AgNW, which is an anisotropic material with low defect density that can act as an electron highway, ensures the relatively high conductivity of the Ag/AgNW composite pattern. , Moreover, AgNWs can provide the mechanical properties to the Ag/AgNW composite pattern necessary to conform to the steps. Figure d–f shows the SEM images which illustrate the role of the AgNWs at the steps.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the conductivity of the formed patterns relies on the concentration of AgNW. The resistance of the pure Ag pattern has a relatively high value because of electron scattering at the many contact points of the Ag granules, whereas AgNW, which is an anisotropic material with low defect density that can act as an electron highway, ensures the relatively high conductivity of the Ag/AgNW composite pattern. , Moreover, AgNWs can provide the mechanical properties to the Ag/AgNW composite pattern necessary to conform to the steps. Figure d–f shows the SEM images which illustrate the role of the AgNWs at the steps.…”
Section: Resultsmentioning
confidence: 99%
“…3. In conducting films, the cause of resistance is the presence of various defects, 30) which, in this case, form a metallic contact area. In pure AgNP films, there are numerous contact areas of AgNPs [Fig.…”
Section: Resistivity Dependence On Sintering Temperature and Agnw Con...mentioning
confidence: 99%
“…In general, gravure offset printing requires viscous inks or pastes that mainly consist of solvents, binders, dispersing agents, and solute particles. 26) Among them, the development of the silver nanoparticle inks for dry offset printing methods is still in its infancy. If we could use appropriate silver nanoparticle inks for gravure offset printing, it would be possible to achieve fine line electrodes with low resistance.…”
Section: Introductionmentioning
confidence: 99%